Modestly protective cytomegalovirus vaccination of young children effectively prevents congenital infection at the population level. Issue 35 (19th August 2022) - Byrne, Catherine; Coombs, Daniel; Gantt, Soren
Abstract: A vaccine to prevent congenital cytomegalovirus infection (cCMV) is a public health priority. cCMV results from maternal primary or non-primary CMV infection (reinfection, or reactivation of chronic infection) during pregnancy. Young children are a major source of transmission to pregnant women because they shed CMV at high viral loads for prolonged periods. CMV vaccines evaluated in clinical trials so far have demonstrated only approximately 50% efficacy against maternal primary infection. None of these have been approved, as higher levels of vaccine efficacy are assumed to be required to substantially reduce cCMV prevalence. Here, we designed a mathematical model to capture the relationship between viral shedding by young children and maternal CMV infections during pregnancy. Using this model, we were able to quantify the impact of CMV post-infection immunity on protecting against reinfection and viral shedding. There was a 36% reduction in the risk of infection to a seropositive person with post-infection immunity (reinfection) versus a seronegative person without this immunity (primary infection), given the same exposure. Viral shedding following reinfection was only 34% the quantity of that following primary infection. Our model also predicted that a vaccine that confers the equivalent of post-infection immunity, when given to young children, would markedly reduce both CMV transmission to pregnant women and the prevalence of cCMV. Thus, we predict that existing vaccine candidates that have been shown to be only modestly protective may in fact be highly effective at preventing cCMV by interrupting child-to-mother transmission.